Corrigendum to ‘Script for resilience analysis in energy systems: Python programming code and partial associated data of four cogeneration plants’ [Data in Brief 36 (2021) 106986] - da Silva, Fellipe Sartori; Matelli, José Alexandre (Data in brief, 2022)
[This corrects the article DOI: 10.1016/j.dib.2021.106986.].